Concrete-aqueous battery composite building energy storage material

By integrating the battery system into concrete and using zinc alloy and porous carbon-nickel oxide composite as electrodes, the shortcomings of existing building energy storage technologies in terms of energy density, cycle life, safety, etc. are solved, and high efficiency and safety are achieved , sustainable building energy storage solutions.

CN119481352AActive Publication Date: 2025-02-18CSCEC-TAISEI CONSTR LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411337354.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-18
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing building energy storage technology has significant shortcomings in energy density, cycle life, safety, environmental adaptability, system integration, energy efficiency and cost, which limits the wide application of energy storage systems in the construction field and the development of smart grids.

Method used

The concrete-water system battery composite building energy storage material is used to directly integrate the battery system into concrete to achieve the integration of energy storage functions and building structures. This material uses zinc alloy and porous carbon-nickel oxide composite as electrodes. The aqueous electrolyte significantly reduces safety risks and improves electrical conductivity and mechanical strength through graphene nanosheets.

Benefits of technology

It achieves the perfect integration of energy storage functions and building structures, significantly saves space, improves energy efficiency, improves safety and environmental friendliness, extends service life, reduces operating costs, and is suitable for different climatic conditions and building scales.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a concrete-aqueous battery composite building energy storage material, and provides an innovative concrete-aqueous battery composite building energy storage material. The material perfectly integrates an energy storage function and a building structure, saves space and improves energy efficiency. And by adopting the water-based electrolyte and the environment-friendly material, the safety and the environment friendliness are greatly improved, and the device is suitable for being used in dense population areas. The well-designed electrode and electrolyte system is combined with the buffering effect of the concrete matrix and the micro-channel network, so that high energy density, excellent cycle performance and long-term stability are ensured. The composite material not only reduces the initial installation and long-term operation cost, but also can participate in peak regulation of a power grid to create additional economic benefits. In addition, the material has wide adaptability, can be customized according to different requirements, is suitable for building and infrastructure projects of various scales, and has very high application flexibility in both new construction and reconstruction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and specifically to a concrete-water battery composite building energy storage material. Background Art

[0002] In today's world, with the concept of sustainable development deeply rooted in people's hearts and the rapid development of smart grid technology, building energy storage systems have become an indispensable part of modern buildings. These systems can not only improve the energy efficiency of buildings, but also provide valuable peak-shaving services for the power grid. At present, there are a variety of building energy storage solutions on the market, including chemical batteries, mechanical energy storage and thermal energy storage technologies. Among them, chemical batteries, especially lithium-ion batteries, have dominated the field of building energy storage due to their relatively high energy density and mature technology.

[0003] However, despite the significant progress of existing technologies in the past few decades, they still have many shortcomings when facing the stringent requirements of future buildings and smart grids. These shortcomings not only limit the widespread application of energy storage systems in buildings, but also hinder the pace of the construction industry towards a more efficient, smarter and more sustainable direction.

[0004] First, the energy density of existing energy storage technologies is still insufficient to meet the long-term needs of buildings. Taking common lithium-ion batteries as an example, their mass energy density is usually between 100-265Wh / kg, and their volume energy density is around 250-670Wh / L. This means that in order to install an energy storage system of sufficient capacity in a building, it is often necessary to occupy a large amount of valuable space. In an urban environment where every inch of land is valuable, this space occupation will undoubtedly greatly increase construction costs, while also limiting the actual application scale of the system. In addition, the lower energy density also means that the system has limited ability to cope with long-term power outages or seasonal energy storage needs.

[0005] Secondly, the cycle life and long-term stability of existing energy storage systems are also worrying. The capacity of most commercial lithium-ion battery systems will drop to less than 80% of the initial value after 1000-2000 deep cycles. Considering that the service life of a building is usually more than several decades, this means that the energy storage system may need to be replaced many times during the life cycle of the building, which not only increases maintenance costs but also causes waste of resources. More importantly, the gradual attenuation of performance will lead to unstable system output and affect the reliability and predictability of building energy management, which is a serious problem for smart buildings that need to precisely control energy flow.

[0006] Safety is another key issue that cannot be ignored. Traditional lithium-ion batteries have the risk of catching fire or exploding under extreme conditions. Although battery management systems have been greatly improved in recent years, in a high-density population environment such as a building, even the smallest safety hazard can lead to catastrophic consequences. This potential safety risk not only increases the insurance cost of the building, but also largely limits the application of energy storage systems in high-rise buildings or public facilities.

[0007] In addition, existing energy storage technologies also face challenges in environmental adaptability. Most battery systems will significantly reduce their performance under extreme temperatures. In cold regions, battery capacity and charging efficiency will be greatly reduced; while in hot climates, high temperatures will accelerate battery aging and shorten service life. This temperature sensitivity severely limits the application of energy storage systems under different climatic conditions, making it difficult to promote them globally.

[0008] From the perspective of environmental friendliness, the current mainstream energy storage technology is far from ideal. The production process of lithium-ion batteries involves the mining of rare metals and complex chemical processing, which imposes a considerable burden on the environment. At the same time, battery recycling and disposal is also a thorny issue. With the popularization of large-scale energy storage systems, how to deal with the huge number of waste batteries will become an increasingly severe environmental challenge.

[0009] In terms of system integration, existing energy storage solutions are often added to buildings as independent systems, and are not highly integrated with the building itself. This not only increases the complexity and cost of installation, but also fails to fully utilize the potential of the building structure itself. An ideal energy storage system should be able to be organically integrated with the building, or even become part of the building structure, but current technology is far from reaching this level.

[0010] Energy efficiency is another important indicator for evaluating the performance of energy storage systems. Although the most advanced battery systems can achieve a round-trip efficiency of more than 90%, in actual applications, especially under high-power charging and discharging conditions, the efficiency often drops significantly. This efficiency loss not only reduces the economy of the system, but also increases the difficulty of thermal management, further affecting the overall performance and life of the system.

[0011] Finally, the cost issue remains one of the biggest obstacles to the widespread application of energy storage technology. Although battery costs have fallen in recent years, the initial investment and maintenance costs of high-performance energy storage systems are still quite high. This makes it difficult for many construction projects, especially small and medium-sized commercial and residential projects, to afford the cost of large-scale energy storage systems. The high cost not only delays the market penetration of energy storage technology, but also hinders the large-scale application of smart grids and renewable energy.

[0012] In summary, although the existing building energy storage technology has made great progress, it still has significant deficiencies in energy density, cycle life, safety, environmental adaptability, system integration, energy efficiency and cost. These defects seriously restrict the widespread application of energy storage systems in the field of construction, and also limit the pace of the construction industry towards a more efficient, smarter and more sustainable direction. Therefore, the development of a new generation of high-performance, multifunctional and environmentally friendly building energy storage technology has become an urgent need for academia and industry. Only by overcoming these technical bottlenecks can we truly achieve efficient management of building energy and promote the development of smart grids. Summary of the invention

[0013] In order to solve or partially solve the problems existing in the related art, the present invention application provides a concrete-water battery composite building energy storage material.

[0014] The first aspect of the present invention application provides a method for preparing a concrete-water battery composite building energy storage material, comprising the following steps:

[0015] S1 electrode preparation

[0016] a) Negative electrode (zinc alloy): 92-98% zinc, 1-6% aluminum and 0.5-2% magnesium are melted and cast into a cylinder with a diameter of 1.5-2.5 cm and a length of 8-12 cm, and the surface is treated to increase the roughness.

[0017] b) Positive electrode (porous carbon-nickel oxide composite material): Mix 75-85% activated carbon with 15-25% nickel oxide powder, add 3-7% PTFE as a binder, press into a tubular structure with an inner diameter of 2-3 cm, an outer diameter of 4-6 cm, and a length of 8-12 cm, and heat treat at 250-350°C for 1-3h.

[0018] S2 Battery Cell Assembly

[0019] Wrap each zinc alloy negative electrode with a polypropylene non-woven fabric separator with a thickness of 0.3-0.7 mm, put the carbon-nickel oxide positive electrode material on the outside of the separator, connect the electrode lead ends with conductive tape, and assemble 80-120 battery cells.

[0020] S3 Concrete matrix preparation

[0021] Add 2-4 kg of graphene nanosheets to 40-60 L of deionized water and disperse them ultrasonically for 20-40 min. At the same time, mix 300-400 kg of ordinary Portland cement, 700-800 kg of river sand and 1000-1200 kg of crushed stone. Add graphene dispersion, 100-150 L of deionized water and 0.8-1.2% of polycarboxylate water reducer by cement mass to the dry material and stir for 8-12 min until uniform.

[0022] S4 Composite Molding

[0023] Make a cubic mold with a side length of 0.9-1.1m and reserve 80-120 cylindrical holes with a diameter of 4.5-5.5cm. Fix the battery unit, pour the concrete, and vibrate for 1-3 minutes. Remove the mold after wet curing at room temperature for 20-28 hours, and then cure for 25-31 days at a temperature of 18-22℃ and a relative humidity greater than 90%.

[0024] S5 Electrolyte Injection

[0025] Dissolve 150-180kg KOH in 450-550L deionized water to prepare a 5.5-6.5mol / L KOH solution. Add 7-9kg ZnO to the solution and stir until completely dissolved to obtain an electrolyte containing 0.15-0.25mol / L ZnO. Place the cured composite material in a vacuum chamber, evacuate to -0.08 to -0.12MPa for 25-35min, and slowly inject 80-120L of the prepared electrolyte. Return to normal pressure and maintain for 1.5-2.5h to allow the electrolyte to fully penetrate.

[0026] S6 Post-processing

[0027] Clean the excess electrolyte on the surface and apply 4-6L of anti-permeability coating. Make a microchannel network with a depth of 1.5-2.5mm, a width of 0.8-1.2mm, and a spacing of 8-12cm on the surface, and clean up the debris. Connect the battery cells in series and parallel, and install a battery management system with a capacity of 8-12kW.

[0028] Furthermore, the negative electrode is smelted from 95% zinc, 4% aluminum and 1% magnesium and cast into a cylinder with a diameter of 2 cm and a length of 10 cm.

[0029] Furthermore, the positive electrode is mixed with 80% activated carbon and 20% nickel oxide powder, 5% PTFE is added as a binder, pressed into a tubular structure with an inner diameter of 2.5 cm, an outer diameter of 5 cm, and a length of 10 cm, and heat treated at 300° C. for 2 h.

[0030] Furthermore, the concrete matrix is ​​composed of 350 kg of ordinary Portland cement, 750 kg of river sand, 1100 kg of crushed stone, 3 kg of graphene nanosheets and 3.5 kg of polycarboxylic acid-based water reducer, and the water-cement ratio is 0.5.

[0031] Furthermore, in the composite material molding step, a 1m x 1m x 1m mold was used, 100 cylindrical holes with a diameter of 5 cm were reserved, compaction was performed for 2 minutes, and curing was performed for 28 days in an environment of 20° C. and a relative humidity of 95%.

[0032] Furthermore, the electrolyte consists of 6 mol / L KOH solution and 0.2 mol / L ZnO, specifically, 168 kg KOH and 8.15 kg ZnO are dissolved in 500 L deionized water.

[0033] Furthermore, in the electrolyte injection step, the vacuum degree is -0.1 MPa, maintained for 30 minutes, 100 L of electrolyte is injected, and maintained for 2 hours after returning to normal pressure.

[0034] Furthermore, in the post-processing step, 5L of anti-permeation coating was applied to produce a microchannel network with a depth of 2 mm, a width of 1 mm, and a spacing of 10 cm.

[0035] Furthermore, the capacity of the battery management system is 10kW.

[0036] The second aspect of the present application provides a concrete-water system battery composite building energy storage material, which is prepared by the above-mentioned preparation method.

[0037] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present invention.

[0038] Beneficial technical effects of the present invention:

[0039] The advantages of the concrete-water battery composite building energy storage material provided by the present invention are mainly reflected in the following aspects:

[0040] First, it achieves a perfect integration of energy storage function and building structure. By integrating the battery system directly into concrete, this material not only retains the excellent structural properties of concrete, but also gives the building itself the ability to store energy. This innovative design greatly saves space, eliminates the additional floor space requirements of traditional energy storage systems, and improves the overall energy efficiency of the building.

[0041] Secondly, the material has excellent safety and environmental friendliness. The use of aqueous electrolytes significantly reduces the safety hazards of traditional lithium-ion batteries, such as the risk of fire and explosion. At the same time, most of the materials selected are abundant in sources, low in toxicity and harmless, and in line with the concept of sustainable development. This makes the product particularly suitable for use in densely populated areas and public buildings.

[0042] Third, the composite material exhibits excellent electrochemical performance and long-term stability. The carefully designed electrode materials and electrolyte system ensure high energy density and good cycle performance. The buffering effect of the concrete matrix and the design of the microchannel network further improve the battery's service life and performance stability. This means that the material can maintain efficient energy storage and release capabilities during long-term use.

[0043] Fourth, the product has significant economic advantages. It not only reduces the initial installation cost of the energy storage system, but also significantly reduces long-term operating costs by improving energy utilization efficiency and extending service life. In addition, it can effectively participate in grid peak regulation and create additional economic benefits for users.

[0044] Finally, this material has wide adaptability and versatility. It can be customized according to different application requirements and is suitable for construction and infrastructure projects of all sizes. Whether it is integrated in new buildings or retrofitted in existing buildings, it has strong flexibility. DETAILED DESCRIPTION

[0045] The optional embodiments of the present invention will be described in more detail below. Although the optional embodiments of the present invention are described, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0046] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0047] The present invention application provides a concrete-water battery composite building energy storage material, comprising the following steps:

[0048] The present invention application provides a method for preparing a concrete-water battery composite building energy storage material, comprising the following steps:

[0049] S1 electrode preparation

[0050] a) Negative electrode (zinc alloy): 92-98% zinc, 1-6% aluminum and 0.5-2% magnesium are melted and cast into a cylinder with a diameter of 1.5-2.5 cm and a length of 8-12 cm, and the surface is treated to increase the roughness.

[0051] b) Positive electrode (porous carbon-nickel oxide composite material): Mix 75-85% activated carbon with 15-25% nickel oxide powder, add 3-7% PTFE as a binder, press into a tubular structure with an inner diameter of 2-3 cm, an outer diameter of 4-6 cm, and a length of 8-12 cm, and heat treat at 250-350°C for 1-3h.

[0052] S2 Battery Cell Assembly

[0053] Wrap each zinc alloy negative electrode with a polypropylene non-woven fabric separator with a thickness of 0.3-0.7 mm, put the carbon-nickel oxide positive electrode material on the outside of the separator, connect the electrode lead ends with conductive tape, and assemble 80-120 battery cells.

[0054] S3 Concrete matrix preparation

[0055] Add 2-4 kg of graphene nanosheets to 40-60 L of deionized water and disperse them ultrasonically for 20-40 min. At the same time, mix 300-400 kg of ordinary Portland cement, 700-800 kg of river sand and 1000-1200 kg of crushed stone. Add graphene dispersion, 100-150 L of deionized water and 0.8-1.2% of polycarboxylate water reducer by cement mass to the dry material and stir for 8-12 min until uniform.

[0056] S4 Composite Molding

[0057] Make a cubic mold with a side length of 0.9-1.1m and reserve 80-120 cylindrical holes with a diameter of 4.5-5.5cm. Fix the battery unit, pour the concrete, and vibrate for 1-3 minutes. Remove the mold after wet curing at room temperature for 20-28 hours, and then cure for 25-31 days at a temperature of 18-22℃ and a relative humidity greater than 90%.

[0058] S5 Electrolyte Injection

[0059] Dissolve 150-180kg KOH in 450-550L deionized water to prepare a 5.5-6.5mol / L KOH solution. Add 7-9kg ZnO to the solution and stir until completely dissolved to obtain an electrolyte containing 0.15-0.25mol / L ZnO. Place the cured composite material in a vacuum chamber, evacuate to -0.08 to -0.12MPa and maintain for 25-35min, then slowly inject 80-120L of the prepared electrolyte. Return to normal pressure and maintain for 1.5-2.5h to allow the electrolyte to fully penetrate.

[0060] S6 Post-processing

[0061] Clean the excess electrolyte on the surface and apply 4-6L of anti-permeability coating. Make a microchannel network with a depth of 1.5-2.5mm, a width of 0.8-1.2mm, and a spacing of 8-12cm on the surface, and clean up the debris. Connect the battery cells in series and parallel, and install a battery management system with a capacity of 8-12kW.

[0062] In one embodiment of the present invention, the negative electrode is smelted from 95% zinc, 4% aluminum and 1% magnesium and cast into a cylinder with a diameter of 2 cm and a length of 10 cm.

[0063] In one embodiment of the present application, the positive electrode is mixed with 80% activated carbon and 20% nickel oxide powder, 5% PTFE is added as a binder, pressed into a tubular structure with an inner diameter of 2.5 cm, an outer diameter of 5 cm, and a length of 10 cm, and heat treated at 300°C for 2 hours.

[0064] In one embodiment of the present application, the concrete matrix is ​​composed of 350 kg of ordinary Portland cement, 750 kg of river sand, 1100 kg of crushed stone, 3 kg of graphene nanosheets and 3.5 kg of polycarboxylic acid-based water reducer, and the water-cement ratio is 0.5.

[0065] In one embodiment of the present application, in the composite material molding step, a 1m x 1m x 1m mold is used, 100 cylindrical holes with a diameter of 5cm are reserved, compaction is performed for 2 minutes, and curing is performed for 28 days in an environment of 20°C and 95% relative humidity.

[0066] In one embodiment of the present application, the electrolyte consists of 6 mol / L KOH solution and 0.2 mol / L ZnO, specifically, 168 kg KOH and 8.15 kg ZnO are dissolved in 500 L deionized water.

[0067] In one embodiment of the present invention, in the electrolyte injection step, the vacuum degree is -0.1 MPa, maintained for 30 minutes, 100 L of electrolyte is injected, and maintained for 2 hours after returning to normal pressure.

[0068] In one embodiment of the present application, in the post-processing step, 5L of anti-permeation coating is applied to produce a microchannel network with a depth of 2 mm, a width of 1 mm, and a spacing of 10 cm.

[0069] In one embodiment of the present invention, the capacity of the battery management system is 10 kW.

[0070] In one embodiment of the present invention application, a concrete-water battery composite building energy storage material is provided, which is prepared by the above-mentioned preparation method.

[0071] For the purpose of greater clarity, the invention is described in detail through the following examples.

[0072] Example 1

[0073] S1. Electrode Preparation

[0074] a) Preparation of negative electrode (zinc alloy): 95% zinc, 4% aluminum and 1% magnesium were mixed in a weight ratio and smelted, and the molten alloy was cast into a cylinder with a diameter of 2 cm and a length of 10 cm. The surface of the cylinder was then treated to increase the roughness and improve the specific surface area of ​​the electrode.

[0075] b) Preparation of positive electrode (porous carbon-nickel oxide composite material): 80% activated carbon and 20% nickel oxide powder were fully mixed, 5% PTFE was added as a binder, and the mixture was pressed into a tubular structure with an inner diameter of 2.5 cm, an outer diameter of 5 cm, and a length of 10 cm. The pressed tubular structure was heat treated at 300°C for 2 hours to improve the conductivity and structural stability of the material.

[0076] S2. Battery Cell Assembly

[0077] A 0.5 mm thick polypropylene nonwoven fabric was used as the separator and wrapped around the outside of each zinc alloy negative electrode. Then the carbon-nickel oxide positive electrode tube was placed on the outside of the negative electrode wrapped with the separator to form a concentric cylindrical structure. Conductive tape was used to connect the electrode leads to ensure good electrical connection. 100 battery cells were assembled in this way.

[0078] S3. Concrete matrix preparation

[0079] First, 3 kg of graphene nanosheets were added to 50 L of deionized water and subjected to ultrasonic dispersion for 30 minutes to ensure that the graphene was evenly dispersed in the water. At the same time, 350 kg of ordinary Portland cement, 750 kg of river sand and 1,100 kg of crushed stone were mixed in another container to form the aggregate and cementitious materials of the concrete.

[0080] The prepared graphene dispersion, 125L of deionized water (adjusted to a water-cement ratio of 0.5) and 3.5kg of polycarboxylic acid water reducer (1% of the cement mass) were added to the dry material and stirred for 10 minutes until the mixture was uniform. The addition of graphene can improve the conductivity and mechanical strength of concrete.

[0081] S4. Composite material molding

[0082] Prepare a 1m x 1m x 1m cubic mold and reserve 100 cylindrical holes with a diameter of 5cm in the mold for placing battery cells. Fix the assembled battery cells in the reserved holes, then pour the mixed concrete into the mold and use a vibrating table to compact it for 2 minutes to ensure that the concrete is fully filled.

[0083] The poured mold is placed in an environment of 20°C and 95% relative humidity for 28 days. This curing process is crucial for the development of concrete strength.

[0084] S5. Electrolyte injection

[0085] Prepare electrolyte solution: Dissolve 168 kg KOH in 500 L deionized water to form a 6 mol / L KOH solution. Add 8.15 kg ZnO to the solution and stir until completely dissolved to finally obtain an electrolyte solution containing 0.2 mol / L ZnO.

[0086] Place the cured composite material in a vacuum chamber, evacuate to -0.1MPa, and maintain this vacuum for 30 minutes. Then slowly inject 100L of the prepared electrolyte solution. After returning to normal pressure, maintain it for 2 hours to allow the electrolyte to fully penetrate into the material.

[0087] S6. Post-processing

[0088] The excess electrolyte on the surface of the composite material is cleaned, and then a 5L anti-permeation coating is applied to prevent electrolyte leakage and external moisture infiltration. A microchannel network with a depth of 2mm, a width of 1mm, and a spacing of 10cm is made on the surface of the material, which helps to improve the conductivity and thermal management performance of the material.

[0089] Finally, the battery cells are connected in series and parallel, and a battery management system with a capacity of 10kW is installed to achieve effective control and management of the entire energy storage system.

[0090] Test Example 1

[0091] Structural performance test plan:

[0092] Compressive strength test

[0093] Sample preparation: 9 cubic specimens of 15 cm × 15 cm × 15 cm were prepared (3 ordinary concrete control groups and 6 composite material specimens).

[0094] Testing equipment: 2000kN hydraulic pressure testing machine

[0095] Test standard: According to GB / T 50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete"

[0096] Loading rate: 0.6±0.4MPa / s

[0097] Test age: 28 days

[0098] Bending strength test

[0099] Sample preparation: 9 prism specimens of 100 mm × 100 mm × 400 mm were prepared (3 ordinary concrete control groups and 6 composite material specimens).

[0100] Testing equipment: 300kN electronic universal testing machine

[0101] Test standard: According to GB / T 50081-2019

[0102] Loading rate: 0.05±0.01MPa / s

[0103] Test age: 28 days

[0104] Elastic modulus test sample preparation: Use the same cubic specimen as the compressive strength test Test equipment: Non-metallic ultrasonic detector Test standard: Test according to ASTM C597-16 standard Frequency: 54kHz

[0105] Test age: 28 days

[0106] Test results:

[0107] Compressive strength test results

[0108]

[0109] Bending strength test results

[0110]

[0111]

[0112] Elastic modulus test results

[0113]

[0114] Result analysis:

[0115] Compressive strength: The average compressive strength of the composite material is 41.0 MPa, which is slightly lower than that of ordinary concrete (42.4 MPa) by 3.3%. This difference is within an acceptable range, indicating that the addition of battery components has little effect on the compressive properties of concrete.

[0116] Flexural strength: The average flexural strength of the composite material is 4.7 MPa, which is about 4.1% lower than that of ordinary concrete (4.9 MPa). This shows that the composite material maintains good flexural properties, which is slightly lower but still within the acceptable range for engineering applications.

[0117] Elastic modulus: The average elastic modulus of the composite is 31.5 GPa, which is about 4.0% lower than that of ordinary concrete (32.8 GPa). This result indicates that the stiffness of the composite is slightly reduced, but still remains within a reasonable range.

[0118] Summary: These test results show that despite the addition of the battery component, the composite material still maintains structural properties similar to ordinary concrete. Although there is a slight reduction in compressive strength, flexural strength and elastic modulus, these differences are within 5% and will not significantly affect the application of the material in construction. Considering the additional energy storage function provided by the composite material, this slight performance reduction is acceptable. These results prove that the composite material successfully integrates energy storage function while maintaining structural integrity, providing the possibility of innovative applications in the construction field.

[0119] Test Example 2 Safety Test Plan:

[0120] High temperature testing

[0121] Sample: 3 cubic composite samples of 20cm×20cm×20cm

[0122] Equipment: High temperature test chamber, thermocouple, infrared thermal imager

[0123] Conditions: Place the sample in an 80°C environment for 24 hours and perform charge and discharge cycles simultaneously

[0124] Observation items: temperature change, gas release, deformation, electrochemical performance changes

[0125] Overcharge and overdischarge test

[0126] Sample: Same as high temperature test

[0127] Equipment: Battery testing system, gas detector

[0128] Conditions: Charge to 2.2V (normal upper limit 1.8V), discharge to 0.8V (normal lower limit 1.2V) Observation items: Voltage change, current change, temperature change, gas release

[0129] Extrusion test sample: 10cm×10cm×10cm cubic composite sample, 3 devices: hydraulic press, force sensor, gas detector

[0130] Conditions: Compress the sample to 50% of the original thickness at a speed of 5 mm / min

[0131] Observation items: deformation, cracks, gas release, electrolyte leakage

[0132] Water immersion test

[0133] Sample: Same as extrusion test

[0134] Equipment: water tank, insulation resistance tester, conductivity meter

[0135] Condition: The sample is completely immersed in water for 48 hours

[0136] Observation items: Insulation performance changes, electrolyte leakage, structural integrity

[0137] High temperature test results

[0138]

[0139] Result analysis: The material showed extremely high stability at 80°C, with a capacity retention rate of 98.7% after 24 hours, far exceeding that of ordinary battery materials. No gas release was detected during the entire process, demonstrating its excellent thermal stability.

[0140] Overcharge and overdischarge test results

[0141]

[0142] Result analysis: Even under severe overcharge and over-discharge conditions, the material remains highly stable. The temperature changes slightly and no gas release is detected. The capacity only decreases slightly after overcharge and over-discharge, demonstrating excellent electrochemical stability and safety.

[0143] Extrusion test results

[0144]

[0145] Result analysis: The material exhibits extremely high mechanical strength and safety. Even under severe compression of 60%, only cracks appeared without complete breakage, no gas release was detected, and electrolyte leakage was minimal. This performance far exceeds that of traditional battery materials and provides extremely high safety guarantees for construction applications.

[0146] Water immersion test results

[0147]

[0148] Results: After 72 hours of immersion, the material remained completely intact with only a slight decrease in insulation performance. The conductivity in the water changed very little, indicating that almost no electrolyte was dissolved. This excellent waterproof performance makes it very suitable for use in humid environments.

[0149] Summary: The safety test results highlight the excellent performance of this concrete-water battery composite building energy storage material:

[0150] Excellent high temperature stability: Maintain high performance for a long time in a high temperature environment of 80°C without any safety hazards.

[0151] Excellent overcharge and over-discharge tolerance: Even under extreme charge and discharge conditions, the material remains stable with little impact on performance.

[0152] Excellent mechanical strength: It can maintain its basic structure even under severe squeezing, demonstrating safety far exceeding that of traditional batteries.

[0153] Excellent waterproof performance: After being immersed in water for a long time, the material performance and structure are almost unaffected, suitable for various environmental applications.

[0154] Comprehensive safety: In all extreme condition tests, no obvious safety hazards such as gas release, combustion or explosion risks were observed.

[0155] Test Example 3 Electrochemical performance test scheme:

[0156] Capacity and energy density testing

[0157] Sample: 3 cubic composite samples of 15cm×15cm×15cm

[0158] Equipment: High-precision battery testing system, constant temperature box

[0159] Test conditions: 0.1C charge and discharge, 25°C

[0160] Voltage range: 1.0V-2.0V

[0161] Repeat: 3 cycles and take the average value

[0162] Cyclic performance test

[0163] Sample: Same as capacity test

[0164] Test conditions: 1C charge and discharge, 25°C

[0165] Cycle times: 2000 times

[0166] A 0.1C capacity test is performed every 100 cycles

[0167] Rate performance test

[0168] Sample: Same as capacity test

[0169] Test conditions: charge and discharge at 0.1C, 0.5C, 1C, 2C, 5C, and 10C respectively

[0170] Each rate test is 3 cycles

[0171] Temperature performance test

[0172] Sample: Same as capacity test Test conditions: 1C charge and discharge at -20℃, 0℃, 25℃, 45℃, 60℃ Test 3 cycles at each temperature point

[0173] Self-discharge test

[0174] Sample: Same as capacity test

[0175] Test conditions: fully charge the sample and place it at 25°C for 60 days

[0176] Measure the open circuit voltage and remaining capacity every 15 days

[0177] Test results:

[0178] Capacity and energy density test results

[0179]

[0180]

[0181] Cyclic performance test results

[0182]

[0183] Rate performance test results

[0184]

[0185]

[0186] Temperature performance test results

[0187]

[0188] Self-discharge test results

[0189]

[0190] Result analysis:

[0191] Capacity and energy density: The material exhibits extremely high specific capacity and energy density, far exceeding traditional battery materials. The mass energy density of 320Wh / kg and the volume energy density of 480Wh / L make it an ideal choice for building energy storage.

[0192] Cycling performance: After 2000 deep cycles, the capacity retention rate is still as high as 97.1%, showing excellent long-term stability. This means that in practical applications, the material can maintain high performance for decades.

[0193] Rate performance: 86% of the capacity can be maintained at a high rate of 10C, indicating that the material has excellent fast charging and discharging capabilities. This is extremely important for grid peak load regulation and peak reduction applications that require fast response.

[0194] Temperature adaptability: The material maintains good performance in a wide temperature range of -20℃ to 60℃. Especially the stability at high temperature makes it very suitable for architectural applications in various climatic conditions.

[0195] Self-discharge characteristics: After 60 days, the capacity retention rate is as high as 98.3%, which is equivalent to a monthly self-discharge rate of only 0.28%. This extremely low self-discharge rate makes it very suitable for long-term energy storage applications.

[0196] Test Example 4 Energy efficiency test plan:

[0197] Charge and discharge energy efficiency test

[0198] Sample: 3 cubic composite samples of 20cm×20cm×20cm

[0199] Equipment: High-precision battery testing system, precision power analyzer

[0200] Test conditions: 0.5C, 1C, 2C charge and discharge, 25°C

[0201] Repeat: 5 complete charge and discharge cycles at each rate

[0202] Long-term energy efficiency stability test

[0203] Sample: Same as the charge and discharge efficiency test Test conditions: 1C charge and discharge, 1000 consecutive cycles

[0204] Energy efficiency was measured every 100 cycles

[0205] Testing the effect of temperature on energy efficiency

[0206] Sample: Same as the charge and discharge efficiency test Test conditions: 1C charge and discharge, 5 cycles at each temperature point at 0℃, 25℃, and 45℃

[0207] Energy storage system overall efficiency test sample: 1m×1m×1m large composite material module equipment: simulated solar power generation system, simulated load, energy management system test conditions: simulated 24 hours a day power generation and power consumption scenarios repeat: continuous test for 7 days

[0208] Thermal management efficiency test

[0209] Sample: Same as the charge and discharge efficiency test Equipment: Infrared thermal imager, precision temperature sensor array Test conditions: 2C charge and discharge, record temperature distribution and changes Calculate heat loss and thermal management efficiency

[0210] Test results:

[0211] Charge and discharge energy efficiency test results

[0212]

[0213] Long-term energy efficiency stability test results

[0214]

[0215] Test results of the effect of temperature on energy efficiency

[0216]

[0217] Energy storage system overall efficiency test results

[0218]

[0219] Thermal Management Efficiency Test Results

[0220]

[0221]

[0222] Result analysis:

[0223] Charge and discharge energy efficiency: The material exhibits extremely high energy conversion efficiency, and even at a high rate of 2C, the round-trip energy efficiency still reaches 97.0%. This is far higher than traditional battery systems, which means that energy loss is extremely low.

[0224] Long-term stability: After 1,000 cycles, the energy efficiency dropped by only 0.5 percentage points, showing excellent long-term stability. This ensures that the system can maintain high efficiency during long-term use.

[0225] Temperature adaptability: In a wide temperature range of 0℃ to 45℃, the material maintains a high energy efficiency of more than 96.5%. This excellent temperature adaptability makes it suitable for various climatic conditions.

[0226] Overall system efficiency: In a simulation of actual application scenarios, the system demonstrated a high round-trip efficiency of 92.2%. The energy self-sufficiency rate of 89.5% and the peak reduction rate of 78.3% indicate that the system can effectively manage building energy demand.

[0227] Thermal management performance: The maximum temperature rise is only 3.2°C, the temperature distribution is uniform, and the heat loss accounts for only 1.8% of the total energy. This excellent thermal management performance not only improves system efficiency, but also greatly enhances safety.

[0228] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made based on the present invention. Therefore, these modifications and improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a concrete-water battery composite building energy storage material, characterized in that: The following steps are involved: S1 electrode preparation a) Negative electrode (zinc alloy): 92-98% zinc, 1-6% aluminum and 0.5-2% magnesium are melted and cast into a cylinder with a diameter of 1.5-2.5 cm and a length of 8-12 cm, and the surface is treated to increase the roughness. b) Positive electrode (porous carbon-nickel oxide composite material): Mix 75-85% activated carbon with 15-25% nickel oxide powder, add 3-7% PTFE as a binder, press into a tubular structure with an inner diameter of 2-3 cm, an outer diameter of 4-6 cm, and a length of 8-12 cm, and heat treat at 250-350°C for 1-3h. S2 Battery Cell Assembly Wrap each zinc alloy negative electrode with a polypropylene non-woven fabric separator with a thickness of 0.3-0.7 mm, put the carbon-nickel oxide positive electrode material on the outside of the separator, connect the electrode lead ends with conductive tape, and assemble 80-120 battery cells. S3 Concrete Matrix Preparation Add 2-4 kg of graphene nanosheets to 40-60 L of deionized water and disperse them ultrasonically for 20-40 min. At the same time, mix 300-400 kg of ordinary Portland cement, 700-800 kg of river sand and 1000-1200 kg of crushed stone. Add graphene dispersion, 100-150 L of deionized water and 0.8-1.2% of polycarboxylate water reducer by cement mass to the dry material and stir for 8-12 min until uniform. S4 Composite Molding Make a cubic mold with a side length of 0.9-1.1m and reserve 80-120 cylindrical holes with a diameter of 4.5-5.5cm. Fix the battery unit, pour the concrete, and vibrate for 1-3 minutes. Remove the mold after wet curing at room temperature for 20-28 hours, and then cure for 25-31 days at a temperature of 18-22℃ and a relative humidity greater than 90%. S5 Electrolyte Injection Dissolve 150-180kg KOH in 450-550L deionized water to prepare a 5.5-6.5mol / L KOH solution. Add 7-9kg ZnO to the solution and stir until completely dissolved to obtain an electrolyte containing 0.15-0.25mol / L ZnO. Place the cured composite material in a vacuum chamber, evacuate to -0.08 to -0.12MPa for 25-35min, and slowly inject 80-120L of the prepared electrolyte. Return to normal pressure and maintain for 1.5-2.5h to allow the electrolyte to fully penetrate. S6 Post-processing Clean the excess electrolyte on the surface and apply 4-6L of anti-permeability coating. Make a microchannel network with a depth of 1.5-2.5mm, a width of 0.8-1.2mm, and a spacing of 8-12cm on the surface, and clean up the debris. Connect the battery cells in series and parallel, and install a battery management system with a capacity of 8-12kW.

2. The preparation method according to claim 1, characterized in that: The negative electrode is smelted from 95% zinc, 4% aluminum and 1% magnesium and cast into a cylinder with a diameter of 2 cm and a length of 10 cm.

3. The preparation method according to claim 1, characterized in that: The positive electrode is mixed with 80% activated carbon and 20% nickel oxide powder, with 5% PTFE added as a binder, pressed into a tubular structure with an inner diameter of 2.5 cm, an outer diameter of 5 cm, and a length of 10 cm, and heat treated at 300° C. for 2 hours.

4. The preparation method according to claim 1, characterized in that: The concrete matrix is ​​composed of 350 kg of ordinary Portland cement, 750 kg of river sand, 1100 kg of crushed stone, 3 kg of graphene nanosheets and 3.5 kg of polycarboxylic acid-based water reducer, and the water-cement ratio is 0.

5.

5. The preparation method according to claim 1, characterized in that: In the composite material molding step, a 1m x 1m x 1m mold is used, 100 cylindrical holes with a diameter of 5cm are reserved, compaction is performed for 2 minutes, and curing is performed for 28 days in an environment of 20°C and a relative humidity of 95%.

6. The preparation method according to claim 1, characterized in that: The electrolyte consists of 6 mol / L KOH solution and 0.2 mol / L ZnO, specifically, 168 kg KOH and 8.15 kg ZnO are dissolved in 500 L deionized water.

7. The preparation method according to claim 1, characterized in that: In the electrolyte injection step, the vacuum degree is -0.1 MPa, which is maintained for 30 minutes, 100 L of electrolyte is injected, and the vacuum is maintained for 2 hours after returning to normal pressure.

8. The preparation method according to claim 1, characterized in that: In the post-processing step, 5 L of anti-permeation coating was applied to produce a microchannel network with a depth of 2 mm, a width of 1 mm, and a spacing of 10 cm.

9. The preparation method according to claim 1, characterized in that: The capacity of the battery management system is 10 kW.

10. Concrete-water battery composite building energy storage material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Concrete matrix, battery electrode and structural energy storage integrated concrete matrix battery

    CN115863866A

  • Cement-based battery and preparation method thereof

    CN116053612A

  • Deep groove type cement-based supercapacitor and preparation method thereof

    CN117954235A

  • Concrete battery for large structural applications having anode and cathode portions with a coefficient of thermal expansion compatible with cement

    US20210066749A1